Entrepreneurial orientation and firm performance in Italian firms: The moderating role of competitive strategy - Galbreath, Jeremy; Lucianetti, L.; Thomas, Ben; Tisch, D. (EMERALD GROUP PUBLISHING LTD, 2020)
© 2020, Emerald Publishing Limited.